PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL ANIMASI ANIMAKER PADA PEMBELAJARAN TEMATIK TERHADAP HASIL BELAJAR KOGNITIF SISWA - Aristantya Rianto, Priscilla Renna; Tampubolon, Budiman; Kresnadi, Hery (Universitas Tanjungpura, 2023)
The aim of this research is to analyze the influence of the use of audiovisual media in subject-based learning on the learning outcomes of class V students at SDN 35 South Pontianak. The method used is an experiment with a pre-experimental design and a non-equivalent control group design. The entire population consists of students in two classes totaling 63 students. The sample for this research was 31 VA students and 32 VB students. Data Collection Techniques Measurement techniques and data collection tools are used to carry out written tests in multiple choice format. Based on data analysis, the average final score for the experimental class was 73.54 points, and the average final score for the control class was 65.25 points. The results of hypothesis testing using the t test (polling variance) are t_(count )= 2.9617, and for dk (31+32-2 = 61) with a significance level of Î± = 5%, t_(table) = 1.6577, This means that t_ (count ) t_(table ), then Ha is accepted. Based on the results of the effect size (ES) calculation, ES = 0.77 is obtained, which is included in the medium criteria. Therefore, it can be concluded that the use of audio-visual media in subject-based learning has a positive impact on the learning outcomes of Class V students at SDN 35 South Pontianak.